2020
DOI: 10.3390/ijms21072266
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of miPEP165a into Arabidopsis Roots Depends on both Passive Diffusion and Endocytosis-Associated Processes

Abstract: MiPEPs are short natural peptides encoded by microRNAs in plants. Exogenous application of miPEPs increases the expression of their corresponding miRNA and, consequently, induces consistent phenotypical changes. Therefore, miPEPs carry huge potential in agronomy as gene regulators that do not require genome manipulation. However, to this end, it is necessary to know their mode of action, including where they act and how they enter the plants. Here, after analyzing the effect of Arabidopsis thaliana miPEP165a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The observed localization of miPEP156a in the nuclei of cabbage plant cells, which was not detected in the case of miPEP165a in A. thaliana (Ormancey et al, 2020), indicates the ability of miPEP156a peptide to efficient nuclear-cytoplasmic transport. The mechanisms of such transport are very conservative in plants and animals (Sorokin et al, 2007; Merkle, 2011).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The observed localization of miPEP156a in the nuclei of cabbage plant cells, which was not detected in the case of miPEP165a in A. thaliana (Ormancey et al, 2020), indicates the ability of miPEP156a peptide to efficient nuclear-cytoplasmic transport. The mechanisms of such transport are very conservative in plants and animals (Sorokin et al, 2007; Merkle, 2011).…”
Section: Resultsmentioning
confidence: 80%
“…It is important that during these processes, miPEP165a cannot penetrate the central cylinder of the root, so it does not enter the phloem. It is correlated with the fact that peptide does not migrate from the roots to the upper part of the plant (Ormancey et al, 2020). Our experiments with the penetration of miPEP156a into cabbage seedlings revealed a different picture.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the upstream of pre-miRNA containing short ORF is possibly polyadenylated for preventing degradation (I) and is exported to cytoplasm for guiding miPEPs synthesis. External miPEPs are supposed to internalize into cytoplasm by endocytosis-associated processes (II) and passive diffusion (III) ( Ormancey et al, 2020 ; Sharma et al, 2020 ). MiPEPs maybe function to transcription factors (TFs), which regulate the transcription of MIR genes (IV and V), resulting in upregulated expression of associated miRNA.…”
Section: Regulatory Functions Of Primary Microrna-derived Peptidesmentioning
confidence: 99%
“…MicroRNAs (miRNAs) play a significant role in the regulation of gene expression. Ormancey et al investigated the role of a miRNA-encoded peptide, miPEP165a, in A. thaliana [ 6 ]. The authors found that passive diffusion followed by an endocytosis process are two functions of entry of miPEP165a.…”
Section: Functional Analysis Of Signaling Componentsmentioning
confidence: 99%